Synergistic Effect between Zr-MOF and Phosphomolybdic Acid with the Promotion of TiF4 Template - Ding, Zhu; Zhang, Xiao Min; Chang, Xue; Wang, Shuo; Wang, Dan-Hong; Zhang, Ming Hui; Zhang, Tian Hao (Molecules (Basel, Switzerland), 2020)
Metal-Organic Framework (MOF) materials are often modified or functionalized, and then the crystal size and morphology of MOF materials are changed. In the process of preparing UiO-66 confined phosphomolybdic acid (PMA) composites (PU), the TiF4-modified PU (PMA + UiO-66) composite catalyst (TiF4-PU) was successfully synthesized by adding titanium tetrafluoride, and the catalytic desulfurization activity was excellent. Similarly, the reaction mechanism was investigated by means of infrared spectroscopy, Raman spectroscopy, XPS, and UV/Vis spectroscopy. The results show that the addition of TiF4 not only changes the appearance and color of the catalyst, but also changes the valence distribution of the elements in the catalyst. The number of oxygen vacancies in the MOF increases due to the addition of TiF4, and more electrons are transferred from the Zr-MOF to PMA to form more Mo5+, which improved the performance of oxidative desulfurization in comparison. Thus, a stronger strong metal-support interaction (SMSI) effect is observed for TiF4-modified PU catalysts. In addition, the quenching experiment of free radicals shows that ·OH radical is the main active substance in the oxidative desulfurization reaction over TiF4-PU catalyst.